Micromorphology and anatomy of the leaf blade: a contribution to the taxonomy of Luziola (Poaceae, Oryzoideae) from the Pantanal, Brazil - Leandro, Thales D. [UNESP]; Scremin-Dias, Edna; Oliveira Arruda, Rosani do Carmo de (Springer, 2016)
Luziola comprises nine monoecious, aquatic species and has its center of diversity in South America. Due to the morphological similarities among Luziola species in the vegetative stage, the micromorphology and anatomy of the leaf blade of five Luziola species were studied to survey potentially useful features for taxon identification. Oryzoid silica bodies; silicified unicellular trichomes with a rounded apex; stomata in furrows on the adaxial surface; a complex midrib consisting of at least two vascular bundles; superposed vascular bundles in the mesophyll; and fusoid cells are features shared by some of these species. Conversely, features unique to a single species include: vertically elongated epidermal cells surrounding pointed unicellular trichomes, flat midrib and leaf margin dimorphism (L. fragilis), and an obtuse leaf blade margin (L. subintegra). L. spruceana and L. subintegra show the greatest micromorphological and anatomical affinity among the five species herein studied, and L. fragilis has the greatest number of unique features. All species are recognized by the structure of the midrib, a strong feature for the identification of taxa within Luziola. A key for the identification of the studied species is presented based on the leaf blade features.
Keywords: Aquatic grasses; Leaf anatomy; Luziolinae; Oryzeae; Poales; Zizaniinae